Implication of feed restriction during growth period on the growth hormone profiles and morphology ovary of quail hen (Coturnix coturnix japonica) - Hertamawati, R.T.; Soedjarwo, E.; Sjofjan, O.; Suyadi, S (Diponegoro University, 2019)
The aim of this research was to evaluate the effect of feed restriction on growth hormone profiles and ovarian morphology during the growth period. Three hundred 14-day-old quails were used. The quails were maintained on two feeding restriction programs: two dietary regimes based on metabolizable energy (ME), R1 = 2900 kcal/kg and R2 = 2800 kcal/kg, and 3 quantitative feed restriction diets, P0 = 100% ad libitum; P1= 90% ad libitum and P2 = 80%ad libitum (n=300). Each group (n=50) was processed with five replications, 10 birds in each replicate. The change in growth hormone was determined at 28, 35, 42, and 49 days of age, while ovarian morphology was determined at sexual maturity. The results indicated that feed restriction induced a significant increase in growth hormone and insulin-like growth factor-1 after re-feeding. There was no significant effect caused by the rationing of metabolizable energy. The number of large yellow follicles was not different between quails fed with 100% ad libitum and 90% ad libitum. However, feed restriction significantly increased the number of small yellow follicles. In conclusion, the feed could be restricted to 90% ad libitum with a 2900 kcal/kg ration of ME and fed during the starter period (14 to 42 days of age) without influencing ovarian morphology in quails.